Sustained interactions between perception and action in visual extinction and neglect: evidence from sequential pointing. - Kitadono, K; Humphreys, G (2009)
Interactions between perception and action were examined by assessing the effects of action programming on extinction and neglect. In an extension of prior work, effects of sequential motor programming were assessed under conditions in which attention was first directed to an ipsilesional stimulus. Despite pointing and reporting a stimulus on the ipsilesional side first, programming a second action to the contralesional side reduced the spatial deficit on report, improving the report of contralesional stimuli (relative to when the patient just pointed to the ipsilesional side) while decreasing the report of ipsilesional items. The data suggest that perception and action interact through motor feedback to early visual coding, helping a patient overcome a lack of visual awareness to contralesional stimuli. This is effective even when attention has to be disengaged from the ipsilesional side suggesting that motor programming decreases ipsilesional capture and exerts a sustained influence on perception.